INTRUSI AIR LAUT DI KABUPATEN PEMALANG - Utomo, Karuniadi Satrijo (Jurnal Teknik Sipil dan Perencanaan, 2011)
One of water suply problem at costal areas of Pemalang Regency is saltwater intrusion. Aims of this study are to predict that saltwater intrusion and its map, also to prepare suitable efforts to reduce that problem. Result of this study shows that saltwater intrusion at unconfined aquifers on coastal areas of Comal and Ulujami Districts will reach 5.8 km length from their shorelines and at their confined aquifers will reach 4.0 km length from their shorelines in 2013. Whilst, saltwater intrusion at both confined and unconfined aquifers on coastal areas of Pemalang, Taman, and Petarukan Districts will only reach less than1 km length from their shorelines in 2013. For reducing that problem in the future, it is important to cultivate mangrove, to control sink discharge from the existing well pumps, and to build more collective deep wells.Satu di antara masalah penyediaan air baku di daerah pantai Kabupaten Pemalang adalah Intrusi  air laut. Tujuan studi ini adalah untuk memprediksi dan memetakan intrusi air laut di wilayah tersebut, serta menyiapkan upaya pengendaliannya. Hasil studi ini menunjukkan bahwa intrusi air laut pada aquifer bebas di Kecamatan Comal dan Ulujami akan mencapai 5,8 km dari garis pantai dan pada aquifer tertekan akan mencapai 4,0 km dari garis pantai di tahun 2013. Sementara itu, intrusi air laut pada aquifer bebas maupun tertekan di Kecamatan Pemalang, Taman, dan Petarukan masih akan mencapai kurangdari 1 km dari garis pantai di tahun 2013. Untuk mereduksi masalah itu di masa datang, penting dilakukan reboisasi mangrove, pengendalian debit pemompaan dari sumur-sumur yang ada, dan membangun sumur-sumur dalam kolektif.